Oxford handbook of medical ethics and law - Smajdor, Anna; Herring, Jonathan; Wheeler, Robert (Consultant neonatal and pediatric surgeon) (Oxford : Oxford University Press, 2021)
This handbook provides a practical and accessible guide to the legal and ethical issues which a medical professional might face. It explains the major ethical theories - consequentialism, deontology, virtue ethics and principlism - and presents a method for moral decision-making, based on the application of theory and critical reasoning. The text sets out the key legal principles governing medical practice including the obtaining of consent; the law of negligence; the principles of confidentiality; the law on organ donation; and the legal regulation of end of life. The book goes on to present a number of'real life' situations in which the ethical and legal principles are applied in a concrete and clear way. The book also contains extracts from the key legislation governing the practice of medicine.
Also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 19, 2021).
Keywords: Medical ethics; Medical laws and legislation -- Great Britain